Just-in-Time Teaching (JiTT-M) of mechanics: Integration of PhET simulations, Feynman approach to problem solving and metacognition through reflection - Sales, Jorge Victor M. (Animo Repository, 2023)
The challenge of competitive learning materials, specialists, and facilities posed a challenge in effective teaching of Calculus-based Mechanics in Senior High School which led to a shallow understanding of the concepts. Furthermore, the limited contact time aggravated the situation as learners’ ability to reflect on their learning had affected its quality and led to misdirection and disconnection as its relevance was never realized by the learner in their personal context. JiTT-M was developed which involved accomplishing a designed worksheet using guided inquiry and reflective questions in conjunction with PhET simulations, Metacognition through Reflection and using the Feynman Method to assess comprehension individually or as a group in class discussions. This research was carried out on the whole Grade 12 population from Catanduanes National High School during the 2023-2024 school year between March to July, 2024. The results indicated a significant improvement in mechanics, mathematics, and metacognition scores. A significant positive direct relationship between perception attitudes, perception mathematics scores, and mathematics scores mechanics scores was detected. Metacognitive strategies exhibited by the learners can be classified as internal and external metacognitive strategies. Problem-solving strategies preferred by the learners were exposure to various problems with varying difficulty levels to build confidence in the learning process. Additionally, learners preferred guided visualization of problem-solving as it helped them understand the concepts involving the variables they were studying.